Роль параметров первого отпуска в повышении стойкости инструмента из стали Р6М5 - Оприщенко, Татьяна Анатольевна; Дьяченко, С. С.; Кузьменко, Елена Алексеевна; Христофоров, Анатолий Ильич; Костик, Виктория Олеговна (Запорізький національний технічний університет, 2011)
Исследовано влияние температурно-временных параметров первого отпуска на структуру и свойства закаленной быстрорежущей стали Р6М5 после второго отпуска. Предложен принцип выбора температуры и выдержки при первом отпуске в зависимости от условий работы инструмента.

The influence of the first tempering time-temperature parameters on the structure and properties of the conditioning high-speed steel Р6М5 after second tempering was investigated. The principle of choosing the first tempering temperature and holding time depending on the tool operating conditions is proposed.
Role of the first tempering parameters in the increase of tool resistance from the high-speed steel R6M5
Keywords: инструмент режущий; сталь быстрорежущая; инструмент штамповой; температура; cutting tool; stamping tool; high-speed steel; temperature; resistance